AN ANALYSIS IMAGE OF WOMEN IN LITTLE WOMEN NOVEL BY “LOUISA MAY ALCOTT” - Afriani Rismauli simanungkalit; Emil Eka Putra (Journal of Education, Linguistics, Literature and Language Teaching, 2020)
The purpose of this research is to provide an overview in the novel by Louisa May Alcott, where the author uses a feminist approach. The method that the author uses in this research is descriptive qualitative ,where the data that the researcher gets from novel quotes and sentences that explain the image of women see from the theory study of Elaine Walter. This novel describe four sisters who were born in Massachusetts where they have different characters and they lost money because their city is going through a civil war. Then because this situation they move to a small New England Town with they mother (Marmee) then they separated from their father because her father participated in the civil war.Keywords: feminism approach, novel, a little women